Special public roads operations with a speed limit of up to 50 km/h. Analysis, review and update of the procedure - Page de la Azuela, Alberto (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2024)
For hundreds of years, Roadside Operational Devices (DOVP) have been used with the aim of preventing or reacting to the commission of infractions or criminal acts. Nowadays, the State Security Forces and Corps (FCSE) carry out this type of Operational Devices on a daily basis, therefore, this final degree thesis has focused on the study and evaluation of the DOVP of the Guardia Civil in comparison with those of other forces, in order to observe their development in terms of technology and operability, and how these aspects relate to and influence the effectiveness and safety of its components. Finally, various updates have been investigated and proposed with the aim of improving them in terms of technology and operability, resulting in more efficient and safer DOVP.